Studi Perencanaan, Pembuatan Dan Pengujian Turbin Aliran Aksial Head Rendah - - Mursalin; Ahmad Syuhada; - Hamdani (Jurnal Teknik Mesin Unsyiah, 2013)
The study is done to get an axial low head turbine design that gave good performance by using flat blade to further simplifying manufacture. The study is consists of three stages. First, designing an axial low head turbine. Second, manufacturing it and the last, testing on turbine performance. The testing that conducted to 3 m head use three kind of discharges, 0,14 l/s, 0,12 l/s, and 0,10 l/s. Three kinds of runners with blade angle, 30o, 35o, and 40o are also use in the testing. Based on the result of the test, it is known that the best efficency, 76%, turbine rotation on 613 rpm and power 2,013 kW is given by the blade angle 40o.